Pengembangan Sexual Assault Panic Button dengan Fitur Perekam Suara dan Gambar serta Notifikasi Pesan dan Koordinat GPS - Nabila Azalia Rahma; Agus Wagyana (Spektral, 2022)
Efforts to prevent cases of sexual violence can be carried out in various ways, one of which is by making a panic button that can be used when in an emergency situation. This panic button is equipped with several features, namely image capture, voice recording, message notifications, and sending GPS location coordinates. The main component used is a push button which is connected to the ESP32 and ESP-32Cam microcontrollers. Other modules used are the Neo - 6M GPS module as a location tracker, the ISD1820 module as a voice recorder, and a buzzer as an alarm generator. The ESP-32Cam module functions to take pictures automatically. When the victim of sexual violence presses the push button on the device, the buzzer will sound as an alarm and the ISD1820 module will start recording sound. Then, ESP32 will send a message via the Telegram application in the form of a warning sign and a Google Maps link obtained from the GPS module. In addition, the push button is also connected to the ESP-32Cam which automatically takes pictures and sends them to the Telegram application. There are 2 tests performed on this panic button. The first is the GPS feature test which was carried out in 2 different conditions with an average distance difference of 3.7765 m at an open location and 13.085 m at a closed location. The second is the calculation of the delay in the process of sending data from the panic button to the telegram application with a delay value of 04.29 seconds in remote testing and a delay of 04.2133 seconds at close range and the average delay value is 04.25 seconds.